Newly Isolated Streptomyces sp. JBS5-6 as a Potential Biocontrol Agent to Control Banana Fusarium Wilt: Genome Sequencing and Secondary Metabolite Cluster Profiles - Jing, Tao; Zhou, Dengbo; Zhang, Miaoyi; Yun, Tianyan; Qi, Dengfeng; Wei, Yongzan; Chen, Yufeng; Zang, Xiaoping; Wang, Wei; Xie, Jianghui (Frontiers in Microbiology, 2020)
Banana is a key staple food and fruit in the world. Development of global banana industry is seriously threatened by Fusarium wilt disease, caused by Fusarium oxysporum f. sp. cubense (Foc). Especially, Foc tropical race 4 (Foc TR4) can infect more than 80% of global banana and plantain. Until now, there are no commercial chemicals or resistant cultivars available to control the disease. Biological control using actinomycetes is considered as a promising strategy. In this study, 88 actinomycetes were isolated from banana orchard without symptom of Fusarium wilt disease for more than 10 years. An actinobacterial strain labelled with JBS5-6 exhibited strong antifungal activities against Foc TR4 and other selected 10 phytopathogenic fungi. Based on the phenotypic and biochemical traits as well as the complete genome analysis, strain JBS5-6 was assigned to Streptomyces violaceusniger. Its extracts obviously inhibited the mycelial growth and spore germination of Foc TR4 by destroying membrane integrity and ultrastructure of cells. The complete genome of strain JBS5-6 was sequenced and revealed a number of key function gene clusters, contributing to biosynthesis of active secondary metabolites. Sixteen chemical compounds were further identified by gas chromatography-mass spectrometry (GC-MS). 5-hydroxymethyl-2-furancarboxaldehyde was one of dominant components in strain JBS5-6 extracts. Moreover, fermentation broth of strain JBS5-6 significantly reduced the disease index of banana seedlings by inhibiting the infection of Foc TR4 in a pot experiment. Hence, strain JBS5-6 will be a potential biocontrol agent for management of disease and exploitation of biofertilizer.